The de Winter Pattern as Pre-Anterior ST-Elevation-Myocardial-Infarction: An Evolution Sequence - Tiyantara, Muhammad Surya; Herdianto, Djoen (Jurnal Kardiologi Indonesia, 2021)
Introduction: The de Winter pattern (dWP) was first described by de Winter and colleagues in 2008 as static pattern associated with anterior myocardial infarction. A recent study showed the evolution sequence of this pattern into typical ST-elevation myocardial infarction (STEMI). This case discussed dWP who present as pre-anterior STEMI. Case Illustration: A-56-year old Male arrived in the emergency room complained chest pain about 3 hours. The patient also complained of diaphoresis, nausea, and fatigue. The patient has a previous history of hypertension. The vital signs were stable with an unremarkable physical examination. The initial electrocardiogram (ECG) revealed sinus rhythm with j-point depression followed by prominent T wave in precordial leads, slight ST-segment elevation in aVR, and loss of precordial R-wave progression. The initial-troponin-T was 31 pg/mL. Follow-up 1-hour after initial ECG showed typical ST-segment-elevation in V1-V4. The patient undergoing thrombolytic, followed by angiography that showed subtotal occlusion in the proximal left anterior descending (LAD) artery, occlusion in the proximal circumflex artery and stenosis in proximal right coronary artery, echocardiography revealed regional wall motion abnormality in the septal and anterior segments and preserved ejection fraction 58%, the patient was discharged after 8-days treated in intensive cardiac care unit. Conclusion: dWP has been shown as static and dynamic pattern in some conditions and associated with acute LAD occlusion. In this case, we showed dWP as early anterior STEMI, recognition of this pattern lead to early reperfusion and better myocardial salvage as anterior STEMI has a poor outcome.